Relationship Between Hypovitaminosis D and Fractures Among Adolescents With Overweight or Obesity. (February 2023) - Segal, David; Ziv, Adi; Meisman, Andrea; Fry, Jordan; Altaye, Mekibib; Gordon, Catherine M.
Adolescents with overweight/obesity are at risk for vitamin D insufficiency and deficiency. Both overweight/obesity and vitamin D insufficiency/deficiency may predispose to fractures. We enrolled 103 participants (53.3% females, 15.9 ± 2.2 years) in a retrospective case-control study to determine whether an association exists between fractures and a low 25-hydroxyvitamin D (25[OH]D) among adolescents whose body mass index (BMI) ≥ 85 percentile. Cases (n = 28) sustaining a low/medium impact fracture were matched to controls (n = 75) without a fracture history. A conditional-logistic regression analysis addressing the common vitamin D insufficiency/deficiency cutoffs was used. Overweight, obesity, and significant obesity rates were 10.7%, 53.4%, and 35.9%, respectively. Mean (±SD) 25(OH)D was 16.5 ± 6.4 ng/mL. In all, 25(OH)D insufficiency rates (level <20 ng/mL) were 70.5%. Matched cases and controls had similar 25(OH)D insufficiency/deficiency rates ( P > .05). Controlling for race and seasonality showed no association between fractures and 25(OH)D insufficiency/deficiency ( P > .05). These data suggest that fractures are not associated with low 25(OH)D levels among adolescents whose BMI ≥ 85th percentile.